Geo-colonizing Mars: A fun way to raise awareness about environment caring and teach Geometry - Arroyo-Cruz, Lorena (2021)
The technological boom in which we are immersed has caused the game rules in education to change to adapt to the new educational needs demanded by society. An increasingly digital age, where speed, change and transformation have become its fundamental characteristics. This article describes a pedagogical strategy that integrates elements, dynamics and games' mechanics in order to increase motivation in learning geometry, making it more active, lasting, meaningful and fun for Primary Education students. This proposal is based on a Breakout called Geo-Colonizing Mars, an immersive game that includes problem solving activities, experimentation, debates, and research related to geometry. The immersion is supported by a narrative that raises awareness about environment caring through videos and interactive material developed with Genially, Kahoot, Edpuzzle and Flippity. To evaluate this proposal, an intervention was carried out with 51 6th year Primary Education students from a public institution in Spain. The results showed a motivational change that led to a proactive attitude towards learning, collaborative work and problem solving